Pengamatan histopatologis pulpa gigi M. nemestrina yang terpapar getah J. curcas - Indrya Kirana Mattulada (DiscoverSys Inc., 2008)
Tooth pain can be overcame by analgetics oraly or topically applied in the toothcavity. One of the topical analgetic is latex of J. Curcas. The purpose of this study wasto evaluate the anti inflammation effect of the latex of J. Curcas under histopathologicobservation. Twenty two teeth of M. Nemestrina were prepared until perforation,then applied the lyophilized latex of J. Curcas into the cavity and covered bytemporary filling.Eugenol was used as comparison. Evaluation was carried out after3, 6 and 24 hours. Monkeys were euthanized and the teeth were extracted. Antiinflammation effect was evaluated under histopathology observation. The result of thisstudy show red blood cells and acute inflammation were found under 3 and 6 hoursobservation, while odontoblastvacuolization cells and lysis of the blood vessels. Theconclusion was chronic inflammation occured might explain pulp pain relieved due tothe the chronic condition followed